Nanoreinforced Hydrogels for Tissue Engineering: Biomaterials that are Compatible with Load‐Bearing and Electroactive Tissues. Issue 8 (14th December 2016) - Mehrali, Mehdi; Thakur, Ashish; Pennisi, Christian Pablo; Talebian, Sepehr; Arpanaei, Ayyoob; Nikkhah, Mehdi; Dolatshahi‐Pirouz, Alireza
Abstract : Given their highly porous nature and excellent water retention, hydrogel‐based biomaterials can mimic critical properties of the native cellular environment. However, their potential to emulate the electromechanical milieu of native tissues or conform well with the curved topology of human organs needs to be further explored to address a broad range of physiological demands of the body. In this regard, the incorporation of nanomaterials within hydrogels has shown great promise, as a simple one‐step approach, to generate multifunctional scaffolds with previously unattainable biological, mechanical, and electrical properties. Here, recent advances in the fabrication and application of nanocomposite hydrogels in tissue engineering applications are described, with specific attention toward skeletal and electroactive tissues, such as cardiac, nerve, bone, cartilage, and skeletal muscle. Additionally, some potential uses of nanoreinforced hydrogels within the emerging disciplines of cyborganics, bionics, and soft biorobotics are highlighted. Abstract : Tissue engineering has evolved considerably with the rise of bioactive nanomaterials, and has given way to numerous hydrogel‐based scaffolds featuring unique properties like electroactivity and flexibility. These nanoreinforced hydrogels steer a powerful trend in the field of tissue engineering with the generation of skeletal, neural, and cardiac tissues exhibiting electromechanical properties similar to the native tissues found in the body.